The Betrayed Age. Violated Adolescence and Criminal Justice in 19th and 20th Centuries (Italian Review of Legal History, 2024)
In this essay, the connection between law and morality in its most pervasive dimension, namely the sexual one, is addressed through the lenses of criminal justice and crimes against the sexual sphere of the person. The central character of the analysis is the ‘typical victim’, that is the ‘teenager’, who brings together multiple elements of fragility, linked to a critical and unknown age (adolescence) and to gender, largely fueled by stereotypes and prejudices that jurisprudence between the nineteenth and twentieth centuries reveals. In particular, age proves to be a very useful analytical device: it allows us to question the sources by introducing a peculiar temporal regime which, anchored to the time of the person, differently interacts (and reacts) with the times of history, including legal history.
Keywords: victims of sex crimes; adolescence; gender stereotyping; history of criminal law; criminal justice.